BUCKLING ANALYSIS OF SKEW PLATES SUBJECTED TO UNIFORM COMPRESSION LOADING - Budiman Budiman (University Of Muhammadiyah Jakarta, 2022)
The main objective of the research work is to present the buckling analysis of plates subjected to uniform compressive load. To obtain accurate results in analysis plate must be free from shear locking, this phenomenon occurs when the ratio of length to thickness ratios plate increases. Many investigations have been carried out on plate elements to see the behavior of a plate in the case of thin plates. In this paper, we investigated plate analysis in the case of buckling analysis using one of the finite element plates, the numerical analysis was conducted on a skew plate with varying length to thickness ratios, and skew angles. The reference solution in the literature will be used to compare the analysis results the level of convergence and plate performance will be obtained.